2021
DOI: 10.1177/23821205211024078
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready to Integrate Artificial Intelligence Literacy into Medical School Curriculum: Students and Faculty Survey

Abstract: Background: The effects of Artificial Intelligence (AI) technology applications are already felt in healthcare in general and in the practice of medicine in the disciplines of radiology, pathology, ophthalmology, and oncology. The expanding interface between digital data science, emerging AI technologies and healthcare is creating a demand for AI technology literacy in health professions. Objective: To assess medical student and faculty attitudes toward AI, in preparation for teaching AI foundations and data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 20 publications
8
75
0
Order By: Relevance
“…Finally, our findings suggest a need to address the knowledge deficit in the definition, capacity, and functions of AI. This could be done by cultivating AI literacy and exposure from childhood [ 60 ] and incorporating the AI curriculum in health care training and upgrading courses [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our findings suggest a need to address the knowledge deficit in the definition, capacity, and functions of AI. This could be done by cultivating AI literacy and exposure from childhood [ 60 ] and incorporating the AI curriculum in health care training and upgrading courses [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Performance expectancy is found to be related to effort expectancy because it is supposed that people were more likely to perceive that one technology is useful if they ease using this technology (29). In literature, previous studies showed that medical students believed that AI would help to enhance the performance of practices and AI would be integrated deeply in healthcare, from administrative works to clinical routine (30)(31)(32)(33). Indeed, medical students are considered to have high AI literacy than current health professionals.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Indeed, medical students are considered to have high AI literacy than current health professionals. A survey in the United States indicated that medical students were more likely to have basic knowledge about AI and prefer to use AI in patient care when comparing to their faculties (31). Another survey in the United Kingdom found that medical students who were taught about AI were more likely to adopt AI in their practices (18).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies -conducted in Europe, the US and South Korea -have explored the formal education and familiarity of medical or healthcare students with respect to digital advances in healthcare, and much of this work consists of single site studies. [8][9][10][11][12][13][14] To better understand and engage with discussion about the benefits, limitations, and ethical dilemmas presented by these tools, today's medical students will need to become more digitally savvy. Equally, as patients make increasing use of healthcare and well-being algorithms, medical students will need to become better prepared to offer patients advice, and to have knowledge about, the robustness of these tools including when algorithms are safe to use.…”
Section: Introductionmentioning
confidence: 99%